Workforce Scheduling with Cyclic Demands and Day-Off Constraints - Baker, Kenneth R.; Magazine, Michael J. (Management Science, 1977)
We examine the problem of scheduling days off in continuous (seven-day-a-week) operations under a variety of day-off policies, when demand for manpower is N on weekdays and n on weekend days. We consider a number of policies governing employee work assignments and in each case we give a formula for the minimum workforce size and a schedule construction algorithm.